Violent Conflict and the Child Quantity-Quality Tradeoff - Apsara Karki Nepal; Martin Halla; Steven Stillman (Institute of Labor Economics (IZA), 2018)
We show that the exposure to war-related violence increases the quantity of children temporarily, with permanent negative consequences for the quality of the current and previous cohort of children. Our empirical evidence is based on Nepal, which experienced a ten year long civil conflict of varying intensity. Our difference-in-differences analysis shows that women in villages affected by civil conflict increased their actual and desired fertility during the conflict by 22 percent, while child height-for-age declined by 11 to 13 percent. Supporting evidence suggests that the temporary fertility increase was the main pathway leading to reduced child height, as opposed to direct impacts of the conflict. This likely occurred because there were more mouths to feed in these households.
Keywords: D74; H56; J13; O10; O12; 330; conflict; violence; quantity-quality model of fertility; height-for-age; Nepal